Introduction to Open Core Protocol Fastpath to System-on-Chip Design - Schwaderer, W David (Springer New York : Imprint: Springer, 2012)
This book introduces Open Core Protocol (OCP), not as a conventional hardware communications protocol but as a meta-protocol: a means for describing and capturing the communications requirements of an IP core, and mapping them to a specific set of signals with known semantics.  Readers will learn the capabilities of OCP as a semiconductor hardware interface specification that allows different System-On-Chip (SoC) cores to communicate.  The OCP methodology presented enables intellectual property designers to design core interfaces in standard ways. This facilitates reusing OCP-compliant cores across multiple SoC designs which, in turn, drastically reduces design times, support costs, and overall cost for electronics/SoCs. Provides a comprehensive introduction to Open Core Protocol, which is more accessible than the full specification; Designed as a hands-on, how-to guide to semiconductor design; Includes numerous, real "usage examples" which are not available in the full specification; Integrates coverage of design methodology discussing why cores are structured the way they are, whereas the official OCP specification only answers what the structure is.